2021
DOI: 10.1016/j.ejso.2020.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcome prediction in individuals with colorectal cancer and diabetes by accurate assessment of vascular complications: Implications for clinical practice

Abstract: Background: Diabetes is considered a risk factor for mortality following a diagnosis of cancer. We hypothesised that the risk will vary due to the heterogeneous nature of the population and accurate classification of vascular complications will improve prediction of clinical outcomes. Methods: The COloRECTal cancer data Repository (CORECT-R) was used to identify individuals with primary colorectal cancer, who underwent surgical resection in England (2005e2016). Diabetes was recorded using ICD10 codes (E10-E14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In addition, we found that diabetes was an independent risk factor for recurrence, especially for systemic recurrence. The similar results were previously reported in the epithelial ovarian cancer [ 10 , 17 ], pancreatic cancer [ 8 , 18 ], breast cancer [ 7 ], gallbladder cancer [ 9 ], colorectal cancer [ 13 , 19 , 20 ], and non-small-cell lung cancer [ 15 ]. However, the exact mechanism of how diabetes affects the prognosis of AC patients who underwent curative pancreaticoduodenectomy remains unclear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, we found that diabetes was an independent risk factor for recurrence, especially for systemic recurrence. The similar results were previously reported in the epithelial ovarian cancer [ 10 , 17 ], pancreatic cancer [ 8 , 18 ], breast cancer [ 7 ], gallbladder cancer [ 9 ], colorectal cancer [ 13 , 19 , 20 ], and non-small-cell lung cancer [ 15 ]. However, the exact mechanism of how diabetes affects the prognosis of AC patients who underwent curative pancreaticoduodenectomy remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, AC patients with diabetes in the current study were more likely to present with a later stage compared with those without diabetes ( p = 0.05). Thirdly, a previous study found that perhaps diabetes complications were the main reason for the poor prognosis of colorectal cancer patients rather than diabetes itself by accurately assessing diabetes complications [ 20 ]. The results might indicate that prognosis of AC patients who have a prolonged diabetes history is more likely to be affected by diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…This has been explored by our group in colorectal cancer, suggesting that presence of complications is associated with both postoperative mortality (90-day) and death during the surgical episode. 84 …”
Section: Discussionmentioning
confidence: 99%
“…Third, although we collected information on body mass indices, we did not have data available on visceral adiposity and muscle radio-density which have been shown to be associated with increased risk of MACCE in colorectal cancer patients [ 30 ]. Lastly, although data on diabetes including medications and glucose concentrations were available, data on diabetic complications was not available which has been associated with adverse post-operative outcomes in colorectal cancer surgery instead of diabetes itself [ 31 ].…”
Section: Discussionmentioning
confidence: 99%